MENGOPTIMALKAN MEDIA DIGITAL DALAM MEMPERTAHANKAN REPUTASI POSITIF PERPUSTAKAAN DI SMKS PGRI 1 NGAWI - Zuhriana Widya Rahayuning Tyas,; Rita Mayang Saputri,; Sholihatus Salamah,; Umi Chofshoh, (re-JIEM (Research Journal of Islamic Education Management), 2025)
Along with the development of the times, libraries are currently facing challenges that require them to maintain their existence. By using electronic devices, an academic can obtain references wherever they are, without having to go to the library. Digital media makes it easy for libraries to share information about the latest collections, library services, and learning resources, while increasing their positive reputation in the eyes of the public. The purpose of this study is to optimize the use of digital media to maintain the positive reputation of the library. This study uses a descriptive qualitative method, namely a research method that describes existing events. The results of this study are that the SMKS PGRI 1 Ngawi Library utilizes digital media by uploading content such as interesting photos and videos on Instagram to promote services and new book collections. In addition, the library also uses automation applications to improve the quality of service.